2009
DOI: 10.1007/s10578-009-0129-x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Depression and Anxiety in Adolescents with Sickle Cell Disease: The Role of Intrapersonal Characteristics and Stress Processing Variables

Abstract: Sickle cell disease (SCD) complications place patients at risk for poor psychosocial adaptation, including depression and anxiety symptoms. This study aimed to test a mediator model based on the Risk and Resistance model to explore the role of intrapersonal characteristics and stress processing variables in psychosocial functioning. Participants were 44 adolescents with SCD, 15 healthy siblings, and 43 primary caregivers, recruited from an East Coast comprehensive sickle cell center. The participants completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…Studies of psychiatric disorders among adolescents with SCD yielded conflicting results (Iloeje 1991;Adedoyin 1992;Armstong et al 1993;Thompson et al 1999;Simon et al 2009). The results of these studies were varied due to the heterogeneity of cohorting among the studied patients as well as the tool used for psychiatric assessment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies of psychiatric disorders among adolescents with SCD yielded conflicting results (Iloeje 1991;Adedoyin 1992;Armstong et al 1993;Thompson et al 1999;Simon et al 2009). The results of these studies were varied due to the heterogeneity of cohorting among the studied patients as well as the tool used for psychiatric assessment.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, some authors found no difference in psychiatric morbidity between a group with sickle-cell disease and controls. For example, Simon et al (2009) suggested that internalizing symptoms among adolescent with SCD and healthy siblings do not differ and were within non-clinical range on a self-reported questionnaire. Also Cepeda et al (1997), through employing a standardized clinical interview based on DSM-III-R criteria reported that adolescents with SCD do not have a greater risk for clinically significant psychiatric disorders than the same-race outpatient clinic controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations